Factors Affecting Household Food Security in Bundelkhand Region of India - Jatav, Surendra Singh; Mubeena, Md (Indian Journal of Extension Education, 2023)
This study assessed the food security status of the households and examined factors influencing food security within the surveyed households. A total of 240 samples were gathered from Lalitpur and Jhansi districts in the Bundelkhand region using a multistage random sampling technique during the period of August to September 2022. The Indicator approach and Binary Logistic Regression methods were used to analyze the data. The results show households belonging to the Jhansi district had a substantially higher level of food security in comparison to the Lalitpur district. The findings show that Socioeconomic and demographic characteristics of surveyed households have a significant role in determining the level of food security. Hence, the development of an appropriate policy to protect households from the adverse effects of natural disaster like drought and health- hazards like COVID-19 are suggested.
Keywords: Binary logistic regression; Bundelkhand region; Food security